Returns to Investment in Ontario University Education, 1960-1990, and Implications for Tuition Fee Policy - Stager, David A. A. (Canadian Journal of Higher Education, 1996)
Because students' university enrolment decisions are influenced by expected returns to their educational investment, policy decisions should be informed by calculations of such returns. Private rates of return, by field of study, for Ontario university graduates in 1990 ranged from 7% (humanities) to 21% (medicine). Returns were generally higher for women than for men. The 1990 results were virtually unchanged from 1985 when there was a sharp reversal of the long-run decline in rates of return that occurred from 1960 to 1980. Alternative assumptions about tuition fee levels show that doubling tuition fees from 1990 levels, or abolishing fees, would change the rates of return by only about two percentage points in either direction. Doubling fees in the major professional faculties would leave rates of return still in excess of returns to arts and science at current fee levels.